Curriculum Development Based on Disaster Mitigation in Schools: A Bibliometric Analysis - Merya Wulansari; Pujianto Pujianto; Aspri Ayu Jarlismi; Arandha May Rachmawati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Natural disasters are sudden events that negatively impact humans and the environment across various sectors. In the education sector, disasters can disrupt learning processes and cause post-disaster psychological distress among students. Therefore, developing a disaster mitigation–based curriculum is crucial to enhance students' understanding and preparedness. This research aims to identify trends in disaster mitigation–based curriculum development in schools. Using a Systematic Literature Review (SLR) and bibliometric analysis on 108 Scopus-indexed publications (2018–2025), this study found a steady increase in the number of publications. The results show that Indonesia is the most productive country, while Australia is the most cited. Topic cluster analysis revealed four main thematic groups. Indonesia’s position in the “Emerging or Declining Themes” quadrant indicates opportunities for further research. Integrating disaster education with local contexts and incorporating local wisdom and technology could serve as potential future research directions.